X-ray parameters of low segmental lordosis of lumbar spine and their relation with sacral and pelvic tilt in frontal plane in patients with sacroiliac joint dysfunction - Staude, Volodymyr; Radzishevska, Yevgenya; Zlatnyk, Ruslan (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Objective: to study X-ray parameters of low segments and lumbar spine lordosis in patients with sacroiliac joint dysfunction with healthy volunteers and to compare these parameters relations with x-rays parameters of pelvic tilt, sacral base tilt in frontal plane. Methods: 26 volunteers (18–34 y. o.) and 50 patients (20 to 71 y. o.) with sacroiliac joint dysfunction were examined. Inclusion criterias were: pain in the area posterior spinae iliac superior, irradiated to groin, buttocks, thigh; more than 3 months history of pain; failure the previous conservative treatment; positive 4 from 6 provocative tests. On X-rays we measured: the angles of the cranial plane of sacrum tilt in frontal plane, pelvis and sacrum rotation around axial plane; the width of sacro-iliac joint space. We studied angles of lumbar, segmental lordosis LIV–LV, LV–SI, Albrecht angle, cranial plane of sacrum tilt in sagittal plane. Results: the average value of SS angle in vertical position was lower in all patients than in volunteers (1st cluster — 37,7°; 2nd — 42,8°; 3rd — 30,8°; 4th — 36,8°; volunteers — 43,5°). Patients of all clusters had larger LV–SI angle than volunteers (1st cluster — 17,3°; 2nd — 18,6°; 3rd — 17,2°; 4th — 15,6°; volunteers — 12,2°). Patients of 1st, 3rd, 4th clusters had smaller LL angle than volunteers in vertical position. Patients of 2nd cluster had the same LL angle as volunteers have (1st cluster — 40,7°; 3rd — 37,2°; 4th — 43,5°; 2nd — 49,3°; volunteers — 48,3°). Conclusions: all patients with sacroiliac joint dysfunction had larger segmental lordosis LV–SI with adjacent sacroiliac joint compare to volunteers. Patients of the the 1st, 2nd, 3rd clusters had larger segmental lordosis LIV–LV than volunteers. Patients of the 1st, 3rd, 4th clusters had smaller lumbar lordosis. The most favorable results were in patients of the 2nd cluster.